Endocrine Disruptors (EDs) regulatory waves: A frictional lens perspective on regulated and emerging markets (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Endocrine-disrupting chemicals (EDCs) are significantly costing humanity, which upshots the increase in disease and disability. However, unlike other toxicant classes — EDCs have yet to be cataloged onto regulations in a mature way across the globe. This manuscript intends to serve up as a compendium of information that endows with an overview of existing regulatory frameworks and policies those deal with EDCs. In particular, it spotlights on frameworks that explicitly address EDCs (i.e., frameworks that consider both adverse effects and their endocrine causes in the assessment of chemical(s)). Precisely frameworks from 12 countries have been acknowledged and information crucial to understanding the basic functioning has been summarized. This information encompasses the general procedures/practices, criteria, and data requirements for EDCs. An attempt has been made to scan not only economic, regulatory policies available for regulated (USA, Europe, Australia, and Japan) and emerging markets (China, Brazil, South Africa, India, Bangladesh, Korea, and Malaysia), but also illustrate perspective for improvement.